The rubber hand illusion: Sensitivity and reference frame for body ownership - Costantini, Marcello; Haggard, Patrick (Consciousness and cognition, 2007)
When subjects view stimulation of a rubber hand while feeling congruent stimulation of their own hand, they may come to feel that the rubber hand is part of their own body. This illusion of body ownership is termed ‘Rubber Hand Illusion’ (RHI). We investigated sensitivity of RHI to spatial mismatches between visual and somatic experience. We compared the effects of spatial mismatch between the stimulation of the two hands, and equivalent mismatches between the postures of the two hands. We created the mismatch either by adjusting stimulation or posture of the subject’s hand, or, in a separate group of subjects, by adjusting stimulation or posture of the rubber hand. The matching processes underlying body ownership were asymmetrical. The illusion survived small changes in the subject’s hand posture, but disappeared when the same posture transformations were applied to the rubber hand. Mismatch between the stimulation delivered to the subject’s hand and the rubber hand abolished the illusion. The combination of these two situations is of particular interest. When the subject’s hand posture was slightly different from the rubber hand posture, the RHI remained as long as stimulation of the two hands was congruent in a hand-centred spatial reference frame, even though the altered posture of the subject’s hand meant that stimulation was incongruent in external space. Conversely, the RHI was reduced when the stimulation was incongruent in hand-centred space but congruent in external space. We conclude that the visual–tactile correlation that causes the RHI is computed within a hand-centred frame of reference, which is updated with changes in body posture. Current sensory evidence about what is ‘me’ is interpreted with respect to a prior mental body representation.